Marketing, morality, and the natural environment - Crane, Andrew (1998)
This thesis is a study of morality in marketing, focusing specifically on marketing in relation to the natural environment, i.e. green marketing. An interdisciplinary approach is adopted, incorporating a broad range of literature pertaining to issues of morality in marketing. The contribution of this literature is analysed, and the green marketing literature is assessed according to the moral perspectives applied. The need for greater insight into the development and communication of moral meanings in the marketing process is thus identified, and an organization culture perspective is articulated by which to effect this in the context of green marketing. This cultural perspective is then used as the basis for the exploratory, empirical research which forms the core of the thesis.